Análisis sobre la influencia de la desintegración familiar en la victimización, violencia y delincuencia de niños y adolescentes en entornos urbanos en la ciudad de Santo Domingo de los Tsáchilas - Pilatásig Loma, José Luis (2025)
Violence is one of the most recurrent problems in today's society, reflected in different forms of violence. The family has strong implications in this, since it is the first environment of socialization of people, which offers them a set of values, and develops in them the capacity of discernment, through critical thinking and criteria in decision making, but when acts of violence and disintegration occur within the family environment, the members of the same, especially the youngest, replicate said violence in their social interactions and in the association or integration to criminal groups or gangs, which impact on the development of criminal behavior, which later influences the increase of different types of crimes. The present research has as general objective: to analyze the influence of family disintegration on the victimization, violence and delinquency of children and adolescents in urban environments in the city of Santo Domingo de los Tsáchilas. For this, a mixed approach methodology, qualitative-quantitative, is applied, using methods of description and observation methods in order to explain different types of phenomena, for which an instrument is used for the application of a survey, through the Google Form platform, for the collection of information, which will then be analyzed. As results, the criterion is established that family disintegration is the main cause of delinquency of children and adolescents in urban environments in the city of Santo Domingo de los Tsáchilas, configuring itself as a real and palpable problem. As conclusions, it is established that family disintegration has an essential connotation in the integral formation of the person, as a human being, in its multiple characteristics, consequently impacting in a negative way.